A Note on Brauer Commutative Monoid: Rajendra Deore, Pritam Gujarathi - Team, Support (Thai Journal of Mathematics, 2014)
The notion of separable semialgebras over a commutative semirings has been defined in [1]. Here we give some new characterisation about central separable semialgebras and introduce the Brauer commutative monoid.